The Spectrum of Glomerulopathy in Jordan - Said Riyad; Hamzeh Yousef; Tarawneh Mesleh (Saudi Journal of Kidney Diseases and Transplantation, 2000)
In this study, we reviewed the records and the histological findings of a total of 350 adequate native kidney biopsies at both the Jordan University Hospital (260 biopsies in the period 1986-1989) and the Jordan Hospital (90 biopsies in the period 1997-1999). There were 187 males (53.4%) and 163 females (46.6%). Their ages ranged between 12-77 years. The nephrotic syndrome was the presenting feature in 194 (55.4%) patients, acute renal failure in 55 (15.7%), hematuria and/or non-nephrotic proteinuria in 45 (12.9%), chronic renal failure in 32 (9.1%) and hematuria alone 24 (6.9%). In the patients with the nephrotic syndrome, 140 (72.2%) had primary nephrotic syndrome. In this group membranoproliferative glomerulonephritis (MPGN) was the most common pathology and was detected in 49 patients (35%) followed by focal segmental glomerulosclerosis (FSGS) in 38 (27.1%). Amyloidosis and systemic lupus erythematosus were the commonest findings among the 54 patients with secondary nephrotic syndrome (40.7% and 38.8% respectively). Rapidly progressive glomerulonephritis was seen in 34.5% of those patients presenting with acute renal failure, while FSGS was seen in 25% of those with chronic renal failure. Finally IgA nephropathy was the major finding among both the 45 patients with hematuria-proteinuria and the 24 patients with isolated hematuria (26.2% and 66.6% respectively).